2021
DOI: 10.3390/catal11111398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Chelating Ligands on the Catalytic Performance of Rh-Promoted MoS2 in the Hydrodesulfurization of Dibenzothiophene

Abstract: Hydrodesulfurization (HDS) is a widely used process currently employed in petroleum refineries to eliminate organosulfur compounds in fuels. The current hydrotreating process struggles to remove organosulfur compounds with a steric hindrance due to the electronic nature of the current catalysts employed. In this work, the effects of adding chelating ligands such as ethylenediaminetetraacetic acid (EDTA), citric acid (CA) and acetic acid (AA) to rhodium (Rh) and active molybdenum (Mo) species for dibenzothiophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…For example, replacement of transition metal sulfide active phases with noble metals has been successfully used. (Zhang et al, 2019a;Majodina et al, 2021). Ru and Pt as additives result in enhanced C-S cleavage activity as was demonstrated when they were added to a Rh-P catalyst and tested on 4,6-DMDBT (Kanda et al, 2022).…”
Section: Improvements In Conventional Hydroprocessing Catalystsmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, replacement of transition metal sulfide active phases with noble metals has been successfully used. (Zhang et al, 2019a;Majodina et al, 2021). Ru and Pt as additives result in enhanced C-S cleavage activity as was demonstrated when they were added to a Rh-P catalyst and tested on 4,6-DMDBT (Kanda et al, 2022).…”
Section: Improvements In Conventional Hydroprocessing Catalystsmentioning
confidence: 95%
“…Majodina et al (Majodina et al, 2021) recently tested a series of catalysts with and without chelating ligands tested for DBT HDS (RhMo x /Al 2 O 3 , x = EDTA, acetic acid, citric acid) and observed the following:…”
Section: Fine-tuning the Active Phases Of The Catalystsmentioning
confidence: 99%
“…Noble metals (Pd, Pt, Ru, Re, Rh, and Ir) have also been widely investigated for deep HDS catalysis due to their high hydrogenation and hydroisomerization activities, Pd and Pt being the most prominent [36,102,103] . Weise et al compared an unpromoted Pt catalyst with a Pt-doped industrial CoMo catalyst and observed a 46% increase in activity in the latter, attributing the increase in catalytic performance to the incorporation of Pt atoms on the terminal edges and corner sites of CoMo [104] . Pt reduced the binding energy of sulfur, favored the formation of CUS, and created sites that are favorable to the adsorption of sterically hindered molecules such as 4,6-DMDBT [104,105] .…”
Section: Improved Hydrodesulfurization Catalystsmentioning
confidence: 99%
“…We recently reported higher HDS of DBT due to a good synergistic effect between Rh promoter and Mo and more MoS 2 /RhMoS phases when we tested a series of RhMo-x/Al 2 O 3 catalysts with different chelating ligand ratios (x = ethylene diamine, tetraacetic acid, acetic acid, citric acid) [104,105] . We attributed high activity to electron donation from Rh to the Mo conducting band, weakening Mo-S bonds and facilitating the formation of CUS [Figure 3].…”
Section: Improved Hydrodesulfurization Catalystsmentioning
confidence: 99%
See 1 more Smart Citation